The Children of Looked After Children : Outcomes, Experiences and Ensuring Meaningful Support to Young Parents In and Leaving Care - Roberts, Louise (Book collections on Project MUSE., 2021)
EPDF and EPUB available Open Access under CC-BY-NC licence. Based on groundbreaking original research, this book provides a comprehensive account of the issues surrounding pregnancy and parenthood for young people in and leaving care, considering the role of state as corporate parent and grandparent.